2015
DOI: 10.2149/tmh.2015-16
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Essential Containers for <i>Aedes</i> Larval Breeding to Control Dengue in Dhaka, Bangladesh

Abstract: Dengue fever (DF), one of the most important emerging arboviral diseases, is transmitted through the bite of container breeding mosquitoes Aedes aegypti and Aedes albopictus. A household entomological survey was conducted in Dhaka from August through October 2000 to inspect water-holding containers in indoor, outdoor, and rooftop locations for Aedes larvae. The objective of this study was to determine mosquito productivity of each container type and to identify some risk factors of households infested with Aed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
63
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 23 publications
11
63
3
6
Order By: Relevance
“…Aedes mosquito showed its preference with tires, the positive composition took up to 28%. The results are consistent with that of research papers on breeding sites [17][18][19][20]. The lowest positive jars in house in our results might have relevant with the vector control work in 2013.…”
Section: Discussionsupporting
confidence: 93%
“…Aedes mosquito showed its preference with tires, the positive composition took up to 28%. The results are consistent with that of research papers on breeding sites [17][18][19][20]. The lowest positive jars in house in our results might have relevant with the vector control work in 2013.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, large containers are often difficult to clean more frequently to enable the interruption and prevention of mosquito life-cycle and mosquito production. Less frequent cleaning provides good breeding sites for dengue vector production [3236]. It is thus not the container type as such that is a factor for consideration but rather the combination of container size, their placement, no or poorly fitted lids and low frequency of cleaning that is the combined determinant of Aedes infestation.…”
Section: Discussionmentioning
confidence: 99%
“…poorer hygiene). Other studies have shown that containers located outdoors are the main dengue vector producers compared to those located indoors [32, 34, 35, 38]. However, in Vietnam, the majority of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The city has the natural and social conditions which provide ample larval development sites for mosquito populations, particularly during the monsoon, rainy seasons. Aedes aegypti , as the primary vector, occupies the overwhelming majority of the wards (administrative units) in Dhaka [30], while the secondary vector– Aedes albopictus –occupies only a few wards in and around the fringe areas [3132]. …”
Section: Methodsmentioning
confidence: 99%